Pengembangan Kemasan Produk Sabun Kopi (Letofie) Sebagai Wujud Pemberdayaan Masyarakat Di Desa Lembantongoa - Nurul Rodiah; Wiri Wirastuti; Harnida Wahyuni Adda (Institut Nalanda, 2023)
The aim of coffee soap product packaging development of Letofie was to increase the product's commercial worth in order to make it technologically advanced and safely packed (packaging). The market, where trading is happened, people are offering to sell used coffee beans (under size of 5) at lower price. Usage of used coffee beans as the primary component for soap production is a form of empowerment in Lembantongoa village.The method used to achieve this aim is to provide knowledge to the people and provide packaging design training to one of the village youth organization. Coffee soap that is ecologically friendly and product packaging designs that are more appealing and impact-resistant are the outcomes of this knowledge-sharing and training activity.